Traditional India: structure and change - Singer, Milton B,Ed (American Folklore Society. Bibliographical and special series,, 1959)
Milton Singer, in this major work Traditional India: Structure & Change has collected, organized and edited the papers contributed to a symposium of studies of India’s changing traditional culture. These studies have two major bonds of unity: one, the underlying unity and continuity of Indian civilization itself, and, the second, method and concept in the study of civilization. In fact, this work expounds Robert Redfield’s recent formulations of how a civilization may be conceived and studied as a ‘structure of tradition’ and answers the question: how are the culture and society of India’s villages related to the Great Traditions of Indian civilization? How does there exist an overwhelming unity and continuityCONTENTS I. The Social Organization of Tradition Hie Brahman Tradition / Daniel Ingalls The Idea of the Martial Råjpýt / John T. Hitchcock Traditions of the Indian Craftsma / Stella Kramrisch The Indian Merchant / Helen Lamb Class and Cultural Traditions in India / W. Norman Brown The Vahîvancå Bårots of Gujarat: A Caste of Genealogists and Mythographers / A. M. Shah and R. G. Shroff Foreword / M. N. Srinivas II. Cultural Performances and Cultural Media The Råm Lîlå / Norvin Hein The Indian Hero as a Vidyådhara / J.A.B. van Buitenen Oral Poets of South India: The Todas / M. B. Emeneau The Forms of Communication in Vîra¹aiva Religion / William McCormack methods of Popular Religious Instruction in South India / V. Raghavan III. Some Problems and Processes of Culture Change The Great Tradition in a Metropolitan Center: Madras / Milton Singer Religion of the Anåvils of Surat / T. B. Naik Some Aspects of Caste in Bengal / Nirmal Kumar Bose Changing Traditions of a Low Caste / Bernard S. Cohn A Tribal People in an Industrial Setting / Martin Orans Cults of the Dead Among the Nåyars / E. Kathleen Gough A Sikh Village / Indera Singh Tribal Cultures of Peninsular India as a Dimension of the Little Tradition: A Preliminary Statement / Surajit Sinha